(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Sufi’s attitude towards the poet is characterized in thoughts and images by the fact that the poet’s experience tends to enrich the sensory existence, while Sufi seeks to realize the annihilation in the absolute. It is one of the differences illustrated by studying Sufi poetry in contrast to the study of another type of poetry, without denying what combined the two and even the existence of a prominent influence between them: the influence of the poet in the Sufi, the influence of the Sufi, and his thoughts on the poet. Hence, we ask the question: the macro image in poetry expressing to us Sufi’s journey to the attic self with the infallibility of seeing the universe, and the vision of the component?, Does Sufi poetry preserve its artistic value-at least-in terms of images and imagination, and in some respects, it tends to be more about the nature of systems than the spirit of poetry? Keywords:images, poetry, mysticism, vision, imagination.